2008
DOI: 10.1093/jpepsy/jsn137
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Health Disparities and Obesity Interventions in Youth

Abstract: Objective This article reviews intervention studies that address health disparities and the increasing rate of obesity in minority youth. The review focuses on interventions that target obesity-related behaviors (diet, physical activity, sedentary behaviors) and adiposity outcomes (body mass index) in minority children and adolescents. Methods A conceptual framework is presented that integrates ecological, cultural, social, and cognitive approaches to reducing obesity in ethnically diverse youth. The review hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 46 publications
2
112
0
1
Order By: Relevance
“…Tailored interventions have the potential to provide specific behavioral feedback based on individuals' response and can be culturally tailored for ethnic minority populations. [29][30][31] This preliminary study suggests that parents found enjoyment in using the tailored website for increasing F&V intake in their African American youth. More largescale efficacy trials are needed, however, to determine whether this parental tailoring approach can improve health behavior outcomes over a longer follow-up.…”
Section: Discussionmentioning
confidence: 75%
“…Tailored interventions have the potential to provide specific behavioral feedback based on individuals' response and can be culturally tailored for ethnic minority populations. [29][30][31] This preliminary study suggests that parents found enjoyment in using the tailored website for increasing F&V intake in their African American youth. More largescale efficacy trials are needed, however, to determine whether this parental tailoring approach can improve health behavior outcomes over a longer follow-up.…”
Section: Discussionmentioning
confidence: 75%
“…3 Meanwhile, multilevel, multicomponent interventions have tended to be more successful. [29][30][31][32] For example, multicomponent interventions that included culturally targeted and tailored components (e.g., health education, diet, physical activity, reduced screen time, behavioral skills, and motivation groups) have shown a greater impact on health behaviors associated with obesity in minority youth than the individual components in isolation. 31 …”
Section: No Single Solutionmentioning
confidence: 99%
“…[4][5][6] Lower recruitment and enrollment rates in health promotion trials among African Americans may, in part, result from the lack of integrating sociocultural values into recruitment strategies. 7,8 Consideration of sociocultural values provides understanding of social, environmental and historical contexts experienced by a group 9,10 and can be used to identify recruitment mediums that are more culturally relevant. Sociocultural values identified as important for African Americans include: religiosity/spirituality, collectivism or family, and a connection with history or ancestors.…”
Section: Introductionmentioning
confidence: 99%